1997
DOI: 10.1093/geronb/52b.4.p187
|View full text |Cite
|
Sign up to set email alerts
|

Adult Age-Group Differences in Recall for the Literal and Interpretive Meanings of Narrative Text

Abstract: This study examined age differences in recall for the literal and interpretive meanings of narrative text. Following presentation of one of two stories rich in both literal and interpretive content, younger (mean age = 19.2 years) and older (mean age = 72.2 years) adults were asked to retell and to interpret the story. Response task order was counterbalanced across participants. When asked to retell a story as close to the original as possible, the younger adults recalled more of the literal propositional cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 29 publications
7
93
0
1
Order By: Relevance
“…There was a main effect of response type [F(1,77) inference is easy to make and the study pace is controlled by the participant (Zacks & Hasher, 1988: Zacks et al, 1987, although older adults may keep active the incorrect inference longer during reading before settling on the correct inference (Hamm & Hasher, 1992). Previous studies have also shown that when participants are asked to recall a story, younger adults' recall is often more reproductive and text based (using specific details), whereas older adults' recall is more reconstructive and interpretive (Adams, 1991;Adams, Smith, Nyquist, & Perlmutter, 1997). In fact, some have argued that there may be motivational or strategic differences between younger and older adults that could explain these different patterns of data (e.g., Perlmutter & Mitchell, 1982;Reder, Wible, & Martin, 1986).…”
Section: Free Recallmentioning
confidence: 99%
“…There was a main effect of response type [F(1,77) inference is easy to make and the study pace is controlled by the participant (Zacks & Hasher, 1988: Zacks et al, 1987, although older adults may keep active the incorrect inference longer during reading before settling on the correct inference (Hamm & Hasher, 1992). Previous studies have also shown that when participants are asked to recall a story, younger adults' recall is often more reproductive and text based (using specific details), whereas older adults' recall is more reconstructive and interpretive (Adams, 1991;Adams, Smith, Nyquist, & Perlmutter, 1997). In fact, some have argued that there may be motivational or strategic differences between younger and older adults that could explain these different patterns of data (e.g., Perlmutter & Mitchell, 1982;Reder, Wible, & Martin, 1986).…”
Section: Free Recallmentioning
confidence: 99%
“…Related to this issue are findings that there is little age difference in gist-based processing (Adams, Smith, Nyquist, & Perlmutter, 1997;Meyer & Rice, 1981;Zelinski, Light, & Gilewski, 1984). Although older adults show marked declines in processing for details from a text, their ability to remember the gist or main point of what they have been presented seems relatively intact (Holland & Rabbitt, 1990;Zelinski et al, 1984).…”
Section: Language Processingmentioning
confidence: 99%
“…Essentially, as processing abilities at the surface form and textbase levels decline, older adults are forced to place a greater emphasis on schema-based knowledge and the situation model level to counteract this deficit. Thus, older adults may be better able to abstract the moral of a story but, at the same time, have poorer memory for the story itself (Adams, 1991;Adams et al, 1997;Narvaez, Radvansky, & Lynchard, 2007). They also seem to utilize background knowledge to make elaborative inferences during recall of a text and respond better to inference-based comprehension questions, relative to younger adults (Miller et al, 2004).…”
Section: Author Notementioning
confidence: 99%
“…For instance, hearing as little as 20% of a target word in context permitted both older and younger adults to recognize it (Wingfield, Aberdeen, & Stine, 1991). Moreover, older (vs. younger) adults' story interpretations were more elaborate and enriched in meaning as evidenced by their retelling and interpretation of recently read stories (Adams, Smith, Nyquist, & Perlmutter, 1997). But while (linguistic and life) experience increases across the lifespan, processing speed and executive functions among others decline (e.g., Calder et al, 2003;Mill, Allik, Realo, & Valk, 2009).…”
Section: Older Adults' Use Of the Visual Context For Language Processingmentioning
confidence: 99%